2012
DOI: 10.1111/j.1574-6941.2012.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Sunken woods on the ocean floor provide diverse specialized habitats for microorganisms

Abstract: Marine waterlogged woods on the ocean floor provide the foundation for an ecosystem resulting in high biomass and potentially high macrofaunal diversity, similarly to other large organic falls. However, the microorganisms forming the base of wood fall ecosystems remain poorly known. To study the microbial diversity and community structure of sunken woods, we analyzed over 2800 cloned archaeal and bacterial 16S rRNA gene sequences from samples with different geographic locations, depths, and immersion times. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
53
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 78 publications
(102 reference statements)
8
53
1
Order By: Relevance
“…In this case, only one specific fraction of the environmental bacterial pool is able to colonize and persist in the wood matrix when colonization starts. This abiotic selection process is called habitat filtering (Webb et al, 2002) and was shown earlier to structure wood fall communities on the sea floor (Fagervold et al, 2012). Interestingly, the level of habitat filtering decreased with time.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this case, only one specific fraction of the environmental bacterial pool is able to colonize and persist in the wood matrix when colonization starts. This abiotic selection process is called habitat filtering (Webb et al, 2002) and was shown earlier to structure wood fall communities on the sea floor (Fagervold et al, 2012). Interestingly, the level of habitat filtering decreased with time.…”
Section: Discussionmentioning
confidence: 91%
“…Wood fall bacterial communities that were early characterized according to their physical action on the wood matrix (Mouzouras et al, 1988;Jurgens et al, 2003), and first described through the isolation of cultivable representatives (Cundell and Mitchell, 1977;Austin et al, 1979), were precisely identified only recently by molecular tools. A large cloning and sequencing effort gave the first insights into the diversity of natural wood fall bacterial and archaeal assemblages (Fagervold et al, 2012). It demonstrated the presence of sequences associated to possible fermenters and sulfide-oxidizing bacteria, as well as the co-occurrence of free-living sulfate-reducing bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As submerged woods become anaerobic after only a few days [15], it is expected that pathways associated to fermentation, with electron acceptors other than oxygen, play a significant role. Indeed, studies on sunken wood in the deep Mediterranean revealed that this substrate can harbor rich bacterial communities [16][18] including fermenting bacteria, microorganisms involved in sulfur cycling and methane production, and new clades of Bacteria and Archaea with unknown physiologies [18]. As the application of molecular techniques has revealed a large diversity of microbes associated to sunken woods, they have also allowed a first understanding of the ecology of sunken wood microbial communities, showing that wood type, immersion time and the environmental conditions surrounding submerged wood may promote contrasted bacterial communities [19], [16][18].…”
Section: Introductionmentioning
confidence: 99%
“…Xylophagous invertebrates physically modify solid wood tissue into three-dimensional habitat attractive to numerous benthic organisms and their predators (Bienhold et al, 2013, Bessette et al, 2014, McClain and Barry, 2014. These pioneer organisms consume oxygen and are responsible for the development of anaerobic chemoautotrophic conditions that in consequence support a growth of microorganisms involved in methane and sulfur cycles (Fagervold et al, 2012).…”
Section: Introductionmentioning
confidence: 99%